Dissensual subjects : memory, human rights, and postdictatorship in Argentina, Brazil, and Uruguay - Rajca, Andrew C. (Critical insurgencies., 2018)
In Dissensual Subjects, Andrew C. Rajca combines cultural studies and critical theory to explore how the aftereffects of dictatorship have been used to formulate dominant notions of human rights in the present. In so doing, he critiques the exclusionary nature of these processes and highlights who and what count (and do not count) as subjects of human rights as a result. Through an engaging exploration of the concept of "never again" (nunca más/nunca mais) and close analysis of photography exhibits, audiovisual installations, and other art forms in spaces of cultural memory, the book explores how aesthetic interventions can suggest alternative ways of framing human rights subjectivity beyond the rhetoric of liberal humanitarianism. The book visits sites of memory, two of which functioned as detention and torture centers during dictatorships, to highlight the tensions between the testimonial tenor of permanent exhibits and the aesthetic interventions of temporary installations there. Rajca thus introduces perspectives that both undo common understandings of authoritarian violence and its effects as well as reconfigure who or what are made visible as subjects of memory and human rights in postdictatorship countries. Dissensual Subjects offers much to those concerned with numerous interlocking fields: memory, human rights, political subjectivity, aesthetics, cultural studies, visual culture, Southern Cone studies, postdictatorship studies, and sites of memory.